2019
DOI: 10.1111/fwb.13388
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of differentiation in the life history and demography of four recently described species of the Brachionus calyciflorus cryptic species complex

Abstract: Brachionus calyciflorus is arguably the most studied freshwater monogonont rotifer. Although it has been recognised as a cryptic species complex for more than a decade, a formal (re‐)description of the four species known so far (B. calyciflorus, Brachionus dorcas, Brachionus elevatus, and Brachionus fernandoi) has only recently been made. Information on the ecology of these species is very scant and fragmented. The aim of this study was to test for ecological divergence between these four species, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 70 publications
8
20
0
Order By: Relevance
“…Our analyses also show that rotifer assemblages are correlated with distance at smaller spatial scales but are more homogenous at the regional level (Table 4). Other papers have reported similar patterns in multiple studies analyzing species assemblages or populations of a single species [147,160,[163][164][165][166][167]. Thus, our results seem to support the Baas Becking Principle-"Everything is everywhere, but, the environment selects"-the ubiquity hypothesis [168].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our analyses also show that rotifer assemblages are correlated with distance at smaller spatial scales but are more homogenous at the regional level (Table 4). Other papers have reported similar patterns in multiple studies analyzing species assemblages or populations of a single species [147,160,[163][164][165][166][167]. Thus, our results seem to support the Baas Becking Principle-"Everything is everywhere, but, the environment selects"-the ubiquity hypothesis [168].…”
Section: Discussionsupporting
confidence: 87%
“…The five species with significant indicator values associated with a combination of five habitat types (L. bulla, P. megalotrocha, L. luna, and C. gibba) possess wide ecological tolerances. Another implication is that these morphospecies likely represent cryptic species complexes [159,160] (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experiments with the two closely related rotifer species Brachionus calyciflorus sensu stricto (s.s.) and Brachionus fernandoi feeding on diets differing in biochemical food quality revealed not only species-specific, but also strainspecific differences in fitness responses, such as population growth, fecundity and survival [35]. Differences in life-history traits between B. calyciflorus s.s. and B. fernandoi feeding on an alga that lacks LC-PUFA have also been demonstrated by Zhang et al [36]. These differences among rotifer strains and species suggest that biochemical constraints may act as evolutionary drivers on physiological traits within the genus Brachionus.…”
Section: Introductionsupporting
confidence: 57%
“…Differences in life histories between sibling species of the B. calyciflorus species complex have been found in response to competition and/or predation risk 84 . A recent study 85 performed under stable food and temperature conditions (24 °C) showed differences in life history traits such as egg and juvenile developmental times, and egg production between these species. As a corollary, they demonstrated that observed differences are consistent across tested clones within species, i.e., they really represent differentiation between the species.…”
Section: Discussionmentioning
confidence: 97%